Less Is More—Cyclists-Triathlete’s 30 min Cycling Time-Trial Performance Is Impaired With Multiple Feedback Compared to a Single Feedback - Bayne, Freya; Racinais, Sebastien; Mileva, Katya; Hunter, Steve; Gaoua, Nadia (Frontiers in Psychology, 2020)
Purpose: The purpose of this article was to (i) compare different modes of feedback (multiple vs single) on 30min cycling time-trial performance in non-cyclist’s and cyclists-triathletes, and (ii) investigate cyclists-triathlete’s information acquisition. Methods: 20 participants (10 non-cyclists,10 cyclists-triathletes) performed two 30min self-paced cycling time-trials (TT, ~5-7days apart) with either a single feedback (elapsed time) or multiple feedback (power output, elapsed distance, elapsed time, cadence, speed and heart rate). Cyclists-triathlete’s information acquisition was also monitored during the multiple feedback trial via an eye tracker. Perceptual measurements of task motivation, ratings of perceived exertion and affect were collected every 5 minutes. Performance variables (power output, cadence, distance, speed) and heart rate were recorded continuously. Results: Cyclists-triathletes average power output was greater compared to non-cyclists with both multiple feedback (227.99±42.02W; 137.27±27.63W; P<0.05) and single feedback (287.9±60.07W; 131.13±25.53W). Non-cyclist’s performance did not differ between multiple and single feedback (p>0.05). Whereas, cyclists-triathletes 30min cycling time-trial performance was impaired with multiple feedback (227.99±42.02W) compared to single feedback (287.9±60.07W; p<0.05), despite adopting and reporting a similar pacing strategy and perceptual responses (p>0.05). Cyclists-triathlete’s primary and secondary objects of regard were power (64.95s) and elapsed time (64.46s). However, total glance time during multiple feedback decreased from the first 5min (75.67s) to the last 5min (22.34s). Conclusion: Cyclists-triathletes indoor 30min cycling TT performance was impaired with multiple feedback compared to single feedback. Whereas non-cyclist’s performance did not differ between multiple and single feedback. Cyclists-triathletes glanced at power and time which corresponds with the wireless sensor networks they use during training. However, total glance time during multiple feedback decreased over time, and therefore, overloading athletes with feedback may decrease performance in cyclists-triathletes.